Scaling Special Education: Challenges and Opportunities for Edupreneurs - BADAMAS, Omoshalewa Lasbat; IFINJU, Isaac O.; OLAWUYI, Bolanle Olabisi; UYANNE, Elizabeth Obiageli (Ilorin Journal of Education, 2025)
The landscape of special education is undergoing significant transformation, driven by the urgent need to provide equitable learning opportunities for students with diverse needs. This paper explores the challenges and opportunities that edupreneurs face in scaling special education initiatives. Through a qualitative thematic analysis of the insight of 9 crucial stakeholders i.e. special education centre administrators, edupreneurs (entrepreneurs whose business venture is centred on education) and technology in education experts, the study identified key obstacles such as funding limitations, regulatory hurdles, and the need for specialized expertise as the major challenges. Despite these challenges, the paper highlights numerous opportunities for innovation and impact, including developing adaptive learning technologies, personalized educational programmes and collaborative partnerships with public and private sectors. The findings suggest that edupreneurs, by leveraging their agility and innovative approaches, can play a pivotal role in expanding access to quality special education. The study concludes with recommendations for edupreneurs on navigating the complexities of scaling their ventures, emphasising the importance of sustainable business models, stakeholder engagement, and continuous improvement in educational practices. This research underscores the potential of edupreneurship to address critical gaps in special education, ultimately contributing to more inclusive and effective learning environments for all students.